The Relationship between Renewable Energy Production and Employment in European Union Countries: Panel Data Analysis - Azretbergenova, Gulmira; Syzdykov, Beybit; Niyazov, Talgat; Gulzhan, Turysbekova; Yskak, Nazira (International Journal of Energy Economics and Policy, 2021)
Renewable energy, which is the type of energy that plays a major role in the development and growth of countries, plays an important role in today’s world, considering that the life of depleted energy resources is finite. Compared to fossil energy sources, except that its source is infinite, a noticeable difference in carbon dioxide emission is seen as the reason for preferring renewable energy sources. Many studies in the literature investigate the relationship between the consumption of renewable energy resources and economic growth. This study was conducted on renewable energy production in 27 European Union member countries explores its impact on employment. In the study, panel ARDL test was conducted with the data for the years 2006-2019. According to the results of the study, renewable energy generation has a positive effect on employment in European Union countries in the long term. In the long run, a 1% increase in renewable energy primary production increases employment by 0.08%. Increasing the use of renewable energy resources should go beyond being a policy recommendation in international conventions. The fact that these resources provide employment in large areas can be a good alternative today with high unemployment rates. Keywords: renewable energy, employment, developed countries, panel ARDL JEL Classifications: O40, Q43, Q40 DOI: https://doi.org/10.32479/ijeep.10744